Genetic and morphological divergence in the warm-water planktonic foraminifera genus Globigerinoides - Morard, Raphaël; Füllberg, Angelina; Brummer, Geert-Jan A.; Greco, Mattia; Jonkers, Lukas; Wizemann, André; Weiner, Agnes K. M.; Darling, Kate; Siccha, Michael; Ledevin, Ronan; Kitazato, Hiroshi; de Garidel-Thoron, Thibault; et al. (PLOS ONE, 2019)
The planktonic foraminifera genus Globigerinoides provides a prime example of a species-rich genus in which genetic and morphological divergence are uncorrelated. To shed light on the evolutionary processes that lead to the present-day diversity of Globigerinoides, we investigated the genetic, ecological and morphological divergence of its constituent species. We assembled a global collection of single-cell barcode sequences and show that the genus consists of eight distinct genetic types organized in five extant morphospecies. Based on morphological evidence, we reassign the species Globoturborotalita tenella to Globigerinoides and amend Globigerinoides ruber by formally proposing two new subspecies, G. ruber albus n.subsp. and G. ruber ruber in order to express their subspecies level distinction and to replace the informal G. ruber “white” and G. ruber “pink”, respectively. The genetic types within G. ruber and Globigerinoides elongatus show a combination of endemism and coexistence, with little evidence for ecological differentiation. CT-scanning and ontogeny analysis reveal that the diagnostic differences in adult morphologies could be explained by alterations of the ontogenetic trajectories towards final (reproductive) size. This indicates that heterochrony may have caused the observed decoupling between genetic and morphological diversification within the genus. We find little evidence for environmental forcing of either the genetic or the morphological diversification, which allude to biotic interactions such as symbiosis, as the driver of speciation in Globigerinoides.